EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW DENGAN PENDEKATAN CTL TERHADAP PRESTASI BELAJAR DAN ASPEK AFEKTIF SISWA PADA MATERI BANGUN RUANG SISI DATAR DITINJAU DARI KEMAMPUAN SPASIAL - Perwira Negara, Habib Ratu; Kusmayadi, Tri Atmojo; Sujadi, Imam (Jurnal Pembelajaran Matematika, 2015)
Abstract: The aims of this research were to find out the different effect of the cooperative learning model of Jigsaw type with CTL approach, the cooperative learning model of Jigsaw type, and the direct learning model towards students mathematics learning achievement and affective aspect on the subject of plane geometry viewed from the students spatial ability, and category of spatial ability consisted of high, medium and low. The research was quasi experimental. The population was all students of grade VIII State Junior High School in Madiun City on the second semester of 2013/2014 academic years. The sample of this research consisted of 261 students. The instrument used to collect data was mathematics achievement test, questionnaire of students affective aspect and spatial ability test. The hypothesis test used unbalanced two ways multivariate analysis of variance. The results of the research were as follows. (1) The cooperative learning model of Jigsaw type with CTL approach and the cooperative learning model of Jigsaw type gaves a better achievement than direct learning model, and the cooperative learning model of Jigsaw type with CTL approach gaves the same achievement as the cooperative learning model of Jigsaw type. (2) The cooperative learning model of Jigsaw type with CTL approach gaves a better achievement than the cooperative learning model of Jigsaw type and direct learning model, and the cooperative learning model of Jigsaw type gaves a better achievement than direct learning model. (3) Students with the high spatial ability had better achievement than students with the medium and low spatial ability, and students with the medium spatial ability had better achievement than students with the low spatial ability. (4) Students with the high spatial ability had better affective aspect than students with the medium and low spatial ability, and students with the medium spatial ability had the same affective aspect as students with the the low spatial ability. (5) On the cooperative learning model of Jigsaw type with CTL approach, Jigsaw type and direct learning model, students with the high spatial ability had better achievement than students with the medium and low spatial ability, and students with the medium spatial ability had better achievement than students with the low spatial ability. (6) On the cooperative learning models of Jigsaw type with CTL approach and Jigsaw type, students with the high, medium and low spatial ability had the same affective aspects. On the direct learning model, students with the high spatial ability had better affective aspects than students with the medium spatial ability, while students with the high and low spatial ability and students with the medium and low spatial ability had the same affective aspects. (7) On students spatial ability high, medium and low, the cooperative learning model of Jigsaw type with CTL approach and the cooperative learning model of Jigsaw type gaves a better achievement than direct learning model, and the cooperative learning model of Jigsaw type with CTL approach gaves the same achievement as the cooperative learning model of Jigsaw type. (8) On students with the high and medium spatial ability, the cooperative learning model of Jigsaw type with CTL approach, Jigsaw type and direct learning model gives the same affective aspect. On students with the medium spatial ability, the cooperative learning of Jigsaw type with CTL approach gaves a better affective aspect than the direct learning model, while the cooperative learning of Jigsaw type with CTL approach and Jigsaw and also the cooperative learning of Jigsaw type and direct learning model gaves the same affective aspect.Keywords: Jigsaw, CTL approach, spatial ability, learning achievement, and affective aspect.